Respuesta :

Answer:

first find h(4)

-3(4)+2= -10

then find h(-10)=

-3(10)+2= 32

Answer is 32

Step-by-step explanation:

Hope this helps!!

Answer:

[tex] \boxed {32}[/tex]

Step-by-step explanation:

[tex]h(n) = - 3n + 2[/tex]

First, we find the value of h(n) when n = 4.

[tex]h(4) = - 3(4) + 2 \\ h(4) = - 12 + 2 \\ h(4) = - 10[/tex]

Next, we want to find the value of h(h(4)). Substitute h(4) in the equation.

[tex]h(4) = - 10\\ h(h(4)) = h( - 10) \\ h(n) = - 3n + 2 \\ h( - 10) = - 3 (- 10) + 2 \\ h( - 10) = 30 + 2 \\ h( - 10) = 32 \\ \boxed {h(h(4)) = 32}[/tex]